Training on Processing Pear Fruit Skin with the Application of Zero Waste to Become a Fruit Skin Chips Product as an Effort to Realize an Ecotourism Village - Setianingsih, Ni Luh Putu Putri; Sudiarta, I Wayan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Abiansemal Dauh Yeh Cani Village is one of the villages in Abiansemal District. Organic waste processing, especially fruit peel waste, is a serious challenge in realizing a sustainable ecotourism village. One example of organic waste that is often overlooked is pear peel. Although pear flesh is widely consumed, the peel is usually considered waste and is thrown away. Pear peel contains fiber, vitamins, and minerals that are beneficial for health. The economic potential of pear peel can be processed into products with added value, such as fruit peel chips. The purpose of the training is to manage organic waste sustainably and apply the principle of zero waste. This training has also equipped participants with technical skills in the processing process, from raw material preparation and drying to packaging.